A review of the usage of deep eutectic solvents as shale inhibitors in drilling mud - Hammad Rasool, M. (Elsevier B.V., 2022)
Shale stabilization is very significant in avoiding any wellbore instability issues during drilling. Water based drilling mud is usually used with mechanical or chemical inhibitors to inhibit shale swelling. Various salts and polymers are used as chemical inhibitors for shale stabilization. Salts such as KCl are required in large quantity and are not environment friendly. Moreover, most polymers degrade at high temperature which render them unsuitable for High temperature High pressure (HTHP) conditions during drilling. This is when ionic liquids (ILs) became popular among researchers due to their tuneable nature and low melting point. However, the recent studies have disclosed that imidazolium based ionic liquids (the most used class of ILs in drilling fluid) is toxic and ILs are generally expensive, and non-biodegradable. The quest of finding a cheaper and greener but equally effective alternative for ionic liquids concluded with the introduction of Deep Eutectic Solvent (DES) in drilling fluid. The usage of DES as a drilling fluid additive is still at its initial stages. This review features the critical summary of utilization of DES for shale inhibitors in drilling fluid. Moreover, a screening criterion has been developed for the selection of DES for shale inhibition studies which is apparently missing in previous studies. A comparative study between recently used ionic liquids and DES as shale inhibitors has also been carried out revealing that ILs and DES have shown shale inhibition upto 94.1 and 91.6 respectively which proves DESs being cheaper and greener are equally effective, but more research is needed to understand the DES-clay interaction in a better way. Â© 2022 Elsevier B.V.